Menyambut Tahun Baru Islam ditengah Kebersamaan Tradisi Pemuda Ziarah 3 Makam Sesepuh Ulama Dusun di Desa Pesawahan untuk Mempererat Tali Silaturahmi - Ayu Fauziah Annisa Putri; Khairunisa Khairunisa; M. Marteen Ilham Gunawan; Reriz Salwa Faya Aulia; Uput Purwaningrum (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The purpose of this writing is the result of community service in Pesawahan Village as well as providing benefits to the community, especially in Pesawahan Village, about the existence of traditions in commemorating the Islamic New Year.  The method used in this research is qualitative.  Data collection techniques were taken by interviewing the parties involved and documentation. Then the next step that researchers do is to check the clarity related to the data that has been obtained, compile the data in accordance with the specified writing systematics, and conduct further analysis. The result of this writing is that many traditions are carried out in Indonesian regions and the area has its own characteristics in Pesawahan. This tradition is carried out to commemorate the Islamic New Year with the aim of establishing friendship and making the community close together this causes the community to live in harmony.